2020
DOI: 10.1111/jnc.15133
|View full text |Cite
|
Sign up to set email alerts
|

The role of Sphingolipids in myelination and myelin stability and their involvement in childhood and adult demyelinating disorders

Abstract: Demyelinating diseases affect both adults and children and encompass a large spectrum of disorders caused by different mechanisms including abnormal autoimmune or inflammatory responses, viral infections, metabolic alterations, genetic defects, etc. In adults, multiple sclerosis (MS) represents the most common demyelinating disease affecting the central nervous system (CNS). Its prevalence is about 50-300 per 100,000 people (Thompson, Baranzini, Geurts, Hemmer, & Ciccarelli, 2018). Despite the great efforts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 116 publications
2
30
0
1
Order By: Relevance
“…Furthermore, satellite glia specifically expressed genes involved in mitochondrial beta-oxidation ( Acaa2, Acadl, Acadm, Acsbg1, Eci1 ) ( Figure 2D, Table S1 ), which produces energy from fatty acids (Barber and Raben, 2019). Schwann cells were strongly enriched for genes involved in myelination (Figure 2E), including genes specific for sphingolipid synthesis ( Fa2h, Samd8, Sptlc2, Ugt8a ) ( Table S1 ), which are abundant myelin components in both central and peripheral nervous systems (Giussani et al, 2021). Schwann cells also expressed fatty acid elongase genes ( Elovl1, Elovl7 ) that were distinct from those expressed in satellite glia ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, satellite glia specifically expressed genes involved in mitochondrial beta-oxidation ( Acaa2, Acadl, Acadm, Acsbg1, Eci1 ) ( Figure 2D, Table S1 ), which produces energy from fatty acids (Barber and Raben, 2019). Schwann cells were strongly enriched for genes involved in myelination (Figure 2E), including genes specific for sphingolipid synthesis ( Fa2h, Samd8, Sptlc2, Ugt8a ) ( Table S1 ), which are abundant myelin components in both central and peripheral nervous systems (Giussani et al, 2021). Schwann cells also expressed fatty acid elongase genes ( Elovl1, Elovl7 ) that were distinct from those expressed in satellite glia ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipids are widely distributed in the organism, including the central and peripheral nervous system [7,8]. The closest association of sphingolipids with neurodegenerative diseases was related to their structural function, especially the glycosphingolipids, as the main component of the plasma membrane of oligodendrocytes and myelin [9]. However, several studies have demonstrated the implication of sphingolipids in several key biological processes such as cellular proliferation and migration, differentiation, autophagy, apoptosis, senescence, and inflammation [8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by multiple genetic alterations in the gene encoding for the enzyme galactosylceramidase (GALC; EC 3.2.1.46) or, in some rare cases, for the Sphingolipid activator protein saposin A (SapA) [ 1 ]. The deficiency of GALC or SapA does not allow the proper functioning of the complex sphingolipid cell pathway, which is especially crucial for myelinating cells [ 2 ]. More specifically, the GALC-SapA complex is also responsible for cleaving the glycosydic linkage of galatosylsphingosine (psychosine or PSY), a highly cytotoxic molecule which is able to insert into the cell membrane, disrupt raft architecture, and presumably deregulate multiple cell signaling cascades [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%